In vitro formation of roots and rhizomes from anther explants of ginger (Zingiber officinale Rosc.) - NAIR, K RAMACHANDRAN, P N CHANDRASEKHARAN (Journal of Spices and Aromatic Crops, 1992)
Anther explants produced callus and profuse roots when cultured in a modified MS Medium containing 2,4-D, and coconut milk and incubated in darkness.